Behavioral responses of zebrafish (Danio rerio) to different 2D non-moving stimuli - Lenzi, Christian; Grasso, Chiara; Nicoara, Mircea; Savuca, Alexandra; Ciobica, Alin; Plavan, Grabriel Ionut; Strungaru, Stefan Adrian (Archives of Biological Sciences, 2020)
Paper description: The behavioral response to social and sexual 2D non-moving images representing conspecifics were examined. Sexually mature fish underwent non-invasive behavioral tests in a cross-maze. Artificial non-moving 2D images were created using photoshop graphics software. We observed significant sex-related differences in zebrafish responses to fixed artificial stimuli. Females showed a statistically significant preference for 2D images of phenotypically less similar individuals. These results improve knowledge on zebrafish visual perception regarding shoaling and mate choice. The paper offers an alternative to use of animals in experimental research. Abstract: Zebrafish (Danio rerio) is considered an experimental model organism with numerous applications in different fields. The mechanisms underlying social and reproductive preferences are complex. Most of the literature on conspecific interactions focus on the chemical communication mediated by scattered signals in the aquatic medium. The aim of this research was to evaluate the behavioral responses induced in the tested animals by artificial social stimuli. We used 20 sexually mature individuals that underwent several non-invasive behavioral tests in a cross-maze. Artificial non-moving 2D images were created for this study, using photoshop graphics software. Ethological measurements were conducted using video-tracking software (EthoVision XT). The findings showed significant sex-related differences in zebrafish responses to fixed artificial stimuli. In particular, females shoaled more with 2D non-moving images representing conspecifics phenotypically more distant (i.e. color) from them. Integrating dimension and number of individual, one large stimulus was preferred over three small stimuli in terms of cumulative and mean duration for males, and only in terms of cumulative duration for females. We concluded that 2D images representing conspecifics, even without movements, can induce a behavioral response in this species. https://doi.org/10.2298/ABS190823065L Received: August 23, 2019; Revised: November 10, 2019; Accepted: November 12, 2019; Published online: December 11, 2019 How to cite this article: Lenzi C, Grasso C, Nicoara M, Savuca A, Ciobica A, Plavan GI, Strungaru SA. Behavioral responses of zebrafish (Danio rerio) to different 2D non-moving stimuli. Arch Biol Sci. 2020;72(1):45-52.